Crescentic membranoproliferative glomerulonephritis in HIV infection; a mini-review with case study - Priti Meena; Vinant Bhargava; Devinder Singh Rana; Anil Kumar Bhalla; Ashwani Gupta; Manish Malik; Pallav Gupta (Society of Diabetic Nephropathy Prevention, 2022)
HIV-related renal diseases have become more evident and easier to treat due to the prolonged survival of patients with HIV infection on antiretroviral therapy (ART). There are multiple factors involved in the pathogenesis of this entity. However, very little has been described regarding secondary membranoproliferative glomerulonephritis and especially a crescentic disease in these patients. Herein, we describe a patient who was incidentally detected to have HIV infection while evaluating for a rapidly progressive renal failure and was detected to have crescentic glomerulonephritis. We have reviewed the literature pertinent to the case in the present report.